Using a formal high-level language and an automated manikin to automatically generate assembly instructions. (1st January 2014) - Mårdberg, Peter; Carlson, Johan S.; Bohlin, Robert; Delfs, Niclas; Gustafsson, Stefan; Högberg, Dan; Hanson, Lars
This paper presents an approach to automatically generate predetermined motion time system (PMTS) based assembly instruction lists from simulations within digital human modelling (DHM) software. A formal high-level instruction language is used to instruct an automated manikin to perform assembly operations. The manikin, the language and the assembled objects are composed into a discrete model. In a post-computational step, the model is used to construct PMTS instruction lists by mapping the manikin motions, assembled objects and the language instructions onto a set of PMTS keywords. The described approach is implemented in the DHM software IMMA and tested on industrial cases of manual assembly in the automotive industry.